2021
DOI: 10.1002/jssc.202100334
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of the ionic chiral selectors for chiral resolution by chromatography, spectroscopy and electrochemistry

Abstract: Ionic chiral selectors have been received much attention in the field of asymmetric catalysis, chiral recognition, and preparative separation. It has been shown that the addition of ionic chiral selectors can enhance the recognition efficiency dramatically due to the presence of multiple intermolecular interactions, including hydrogen bond, π-π interaction, van der Waals force, electrostatic ion-pairing interaction, and ionic-hydrogen bond. In the initial research stage of the ionic chiral selectors, most of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 184 publications
(185 reference statements)
0
11
0
Order By: Relevance
“…Up to now, numerous methodologies have been applied to the discrimination of a pair of enantiomers, including chromatography, spectroscopy, the electrochemistry method, and the colorimetric method [ 10 , 11 ]. Among these methods, the feasibility of enantioselective discrimination based on stereospecific interaction is highly dependent on the affinity of chiral selectors, such as chiral columns, chiral electrodes, and chiral substrates [ 12 , 13 ]. The chiral selectors with the proper structure and molecular polarity are indispensable for sensitive and specific enantioselective discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, numerous methodologies have been applied to the discrimination of a pair of enantiomers, including chromatography, spectroscopy, the electrochemistry method, and the colorimetric method [ 10 , 11 ]. Among these methods, the feasibility of enantioselective discrimination based on stereospecific interaction is highly dependent on the affinity of chiral selectors, such as chiral columns, chiral electrodes, and chiral substrates [ 12 , 13 ]. The chiral selectors with the proper structure and molecular polarity are indispensable for sensitive and specific enantioselective discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, cationic CD derivatives typically include pyrrolidinium [29,30], amino [26,[31][32][33] groups, or imidazolium [34][35][36] that provide a positive charge. These derivatives of CD can be effective chiral selectors for NSAID separation due to the presence of an aromatic system that can contribute to enantioseparation via π-π interaction between imidazolium cation and ketorolac also containing an aromatic system [37]. The authors [34] have shown that mono-6-deoxy-(alkyl-imidazolium)-β-CD tosylate can be successfully used for the enantioseparation of dan-syl amino acids at BGE pH 8, where amino acids are in anionic form.…”
Section: Introductionmentioning
confidence: 99%
“…More special articles will be found in this issue as well as in those to come.] been developed for the efficient enantiorecognition of chiral probes, [13][14][15] their coupling to delivery systems is still a challenge. An interesting approach is to combine the outstanding enantiorecognition capability of inherently chiral conducting polymers with the highly efficient electromechanical actuation of polypyrrole, [16][17][18][19] triggered by bipolar electrochemistry (BE).…”
Section: Introductionmentioning
confidence: 99%
“…As such, enantiomeric interactions ultimately control and perturb biological functions; thus, enantiorecognition is of tremendous importance in biological systems. Although different spectroscopic methods have been developed for the efficient enantiorecognition of chiral probes, 13–15 their coupling to delivery systems is still a challenge. An interesting approach is to combine the outstanding enantiorecognition capability of inherently chiral conducting polymers with the highly efficient electromechanical actuation of polypyrrole, 16–19 triggered by bipolar electrochemistry (BE).…”
Section: Introductionmentioning
confidence: 99%